Hybrid superplastic forming of AZ31 magnesium alloy - Guo, Meiling (2017)
Hybrid superplastic forming (SPF) has recently been developed as a sheet forming technique, combining a hot drawing (mechanical pre-forming) process and a gas forming process. The hot drawing stage greatly enhances the formability and the forming efficiency of the metal sheet. The blank sheet with a desired amount of material is drawn into the die to form an intermediate hollow shape by a punch. During the gas forming stage, the mechanical pre-formed part is further formed at a target strain rate by applying the gas pressure. It is considered as an efficient way to form components with complex shapes in automotive and aerospace industries.